Normative Construction of Notarial Supervision over the Obligation to Actually Perform Notarial Office - Solikatin, Devi; Jauharoh, Indah Dwi Qurbani, Arini (International Journal of Business, Law, and Education, 2026)
The obligation of a notary to actually perform his or her office, as stipulated in Article 7 paragraph (1) letter a of the Indonesian Notary Office Law, constitutes a legal norm with significant implications for legal certainty and public protection. However, the provision does not provide clear, measurable, and operational indicators regarding the meaning of “actually performing the office.” This article aims to analyze the normative weaknesses of the existing regulation and to formulate an ideal supervisory model for notaries who do not actually perform their official duties. This study employs normative legal research using statutory, conceptual, and case approaches. The findings indicate that the absence of objective indicators, the lack of a specific examination mechanism, and the unavailability of routine monitoring systems have rendered notarial supervision ineffective and overly dependent on public complaints. This situation creates legal uncertainty and weakens legal protection for members of the public who require notarial services. This article argues that the phrase “actually performing the office” should at least include the existence of an active office, the physical presence of the notary, the real exercise of notarial authority, the readiness of administrative records and notarial protocols, and the openness of services to the public. Furthermore, an operational, structured, and objectively measurable supervisory mechanism is required to strengthen the effectiveness of supervision and to ensure legal certainty and public protection.